SOA-PE: A service-oriented architecture for Planning and Execution in cyber-physical systems - Feljan, Aneta Vulgarakis; Mohalik, Swarup Kumar; Jayaraman, Mahesh Babu; Badrinath, Ramamurthy (2015 International Conference on Smart Sensors and Systems (IC-SSS), 2015)
In this paper, we suggest a service-oriented architecture for planning and execution (SOA-PE) in large scale cyber-physical systems (CPS). SOA-PE provides a clean separation between domain modeling, planning, execution, monitoring and actuation services. This approach helps realize the system-of-systems paradigm allowing the decomposition of system goals into smaller subgoals, thus enhancing the scalability of the proposed solution. In addition to supporting large scale, autonomous systems, the service-oriented approach provides several benefits such as reusability, independent development and deployment, platform independence, transparency and flexibility, to the core services of Planning and Execution in these systems. The architecture targets decentralized, multi-agent systems for solutions like smart transportation and logistics and can scale to larger IoT use cases like smart cities. We illustrate the functionalities of the architecture through a prototype implementation and a case study from the logistics domain.